FABRICATION ASPECT PRICING OF SCREW TURBINE FOR A MICRO HYDRO ELECTRICAL GENERATOR - Hendra, Hendra; Surbakti, Filo C (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
Screw turbine for a micro hydro power generator (PLTMH) is to utilize  water flow as electricity generator by screw rotation. The screw was made in two parts, each consists of shaft and blade. The dimension (mm) was 1300 length, 165.5 diameter of shaft axis and 200 blade height with 5 thickness. The first part was different from the second in number and pitch of the blades. The first consists of 5 blade plates by 260 pitch, the second one 7 blades by 185.7 pitch. The fabrication of the screw was completed through series of processes, i.e. plate cutting, plate flatening, pressing, rolling, welding, and balancing. The first part costed Rp. 12.780.000 and the second one Rp. 13.430.000.